Сортозалежні ростові показники та регенераційна здатність різних експлантів капусти в культурі in vitro - Тараненко, А.М.; Банникова, М.О.; Моргун, Б.В. (Фактори експериментальної еволюції організмів, 2014)
Aims. High nutritional and economic value of cabbage makes it an attractive model for biotechnology research. Thus, we were engaged in the selection of cabbage varieties, with the aim to get the transgenic cabbage in future. Methods. Using commercial fungicides, we established the conditions for the germination of seeds which prevent the development of fungal and bacterial infection of seeds. In addition we tested and selected nutrient media for regeneration of different explants of cabbage. As a basic medium the MS was used with various concentrations of plant growth regulators. Results. The conditions of growth and in vitro establishment of 19 varieties of cabbage have been studied. It was shown that the highest percentage of regeneration occurred when using the cabbage hyppocotyl explants of Langedijker (81.8 ± 2.71%) and Kharkivska zymova (78.7 ± 1.97%) varieties but the best results were obtained for 5 varieties. Conclusions. The optimum compositions of regenerative medium for each variety were defined. Explants of Langedijker and Kharkivska zymova will be used for the further genetic transformation experiments.